2008
DOI: 10.1359/jbmr.080231
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Anabolic Effects of Teriparatide on Bone: Insight From the Treatment of a Patient With Pycnodysostosis

Abstract: Pycnodysostosis is an extremely rare genetic osteosclerosis caused by cathepsin K deficiency. We hypothesized that teriparatide, a potent anabolic agent used in the treatment of osteoporosis, might reduce skeletal fragility by activating bone turnover. We studied a typical case of pycnodysostosis in a 37-yr-old woman who exhibited short stature, skull and thorax deformities, and a history of severe fragility fractures. Cathepsin K gene sequencing was performed. Before and after 6 mo of 20 g/d teriparatide, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…This line is further supported by a recent case report testing the activity of parathyroid hormone (PTH) in a pycnodysostotic patient. Consistent with the distorted bone formation seen in cathepsin K deWcient individuals, PTH showed no anabolic activity (Chavassieux et al 2008), supporting the hypothesis that bone formation cannot occur in resorption pits containing high levels of collagen Wbers.…”
Section: Cathepsin Kmentioning
confidence: 53%
See 1 more Smart Citation
“…This line is further supported by a recent case report testing the activity of parathyroid hormone (PTH) in a pycnodysostotic patient. Consistent with the distorted bone formation seen in cathepsin K deWcient individuals, PTH showed no anabolic activity (Chavassieux et al 2008), supporting the hypothesis that bone formation cannot occur in resorption pits containing high levels of collagen Wbers.…”
Section: Cathepsin Kmentioning
confidence: 53%
“…Biochemical markers of bone turnover in pycnodysostosis demonstrated that the level of the cathepsin K generated type I collagen fragment (CTX-I) was greatly reduced, whereas the MMP generated type I collagen fragment (ICTP) was present in high amounts, indicating compensation by these proteases (Nishi et al 1999) In vitro cultured cathepsin K deWcient osteoclasts showed complete absence of CTX-I release (Chavassieux et al 2008). Compensation for lack of cathepsin K activity by MMPs is also seen in cultures of human osteoclasts challenged with the cysteine proteinase inhibitor E64 Henriksen et al 2006;Sassi et al 2000), a phenomenon also seen in cathepsin K deWcient mice (Kiviranta et al 2005).…”
Section: Cathepsin Kmentioning
confidence: 99%
“…Furthermore, since tissue age is a key determinant of bone's damage morphology and is, in turn, related to bone turnover, a greater emphasis has been placed on the post-translational modifications of protein components and the increase in the mean degree of tissue mineralization, or DMB. Again through a number of studies over the last decade, the group in Lyon has demonstrated that reduced bone turnover increases DMB in a number of clinical situations including, but not limited to, bisphosphonate treatment [33] and cathepsin K deficiency [34]. DMB content also increases with tissue age and is consequently higher in interstitial than in the osteonal bone compartment, but an association between DMB and microdamage morphology or between DMB and bone fracture properties has not been established.…”
Section: Bone Matrix and Vertebral Fragilitymentioning
confidence: 99%
“…Although histomorphometry shows a markedly increased bone mass, bone forming indices (e.g. mineral apposition rate and bone formation rate) have been reported to be low in individuals with a cathepsin K mutation, and quite unresponsive to intermittent PTH [40]. The experimental evidence summarized below, however, suggests differently.…”
Section: Cathepsin Kmentioning
confidence: 99%